Physico-Chemical Changes in Cavendish Banana (Musa Cavendishii L. Var. Montel) During Fruit Development, Maturation and Storage - Mustaffa, Razali (1997)
Studies on the physico-chemical changes between different hand positions (top, middle and bottom) within a bunch and different finger positions (upper and lower) within a hand at different maturity stages (between 3 to 15 weeks from the appearance of flower emergence) were carried out on 'Montel' banana (Musa cavendishii L). The size, weight, volume and peel colour of fruits increased significantly (P<0.01) for fruits from all positions (hands and fingers within a hand) within a bunch until the end of maturity stage. On the other hand, fruit texture decreased significantly (P<0.01). The total soluble solids (TSS), ascorbic acid (AA) and sugar contents increased slowly during development, but the increase was rapid during ripening. The starch composition accumulated gradually (P<0.05) at the early stages and decreased thereafter. The pH and titratable acidity values showed an irregular pattern in an the fruits from an positions during the maturity stage. There was a significant decrease (P<0.01) in the tannin content between the different portions of hands within a bunch and between different fingers within a hand at maturity. There was an increase in AIS at the early stages, but after approaching maturity (week 12), it decreased significantly (P<0.05) in the ripe fruits. The pectins increased at the early stages until a maximum at week 12 and then slowly decreased. At the end of maturity stage, the pectic substances started to increase slowly until the ripening stage. The suitable harvesting stage was found to be between 12 to 15 weeks after flower emergence. Postharvest treatment with liquid paraffin, clingwrap, low density polyethylene (LDPE) with and without potassium permanganate (KMn04) were studied to extend the shelf life of 'Montel' banana (Musa cavendishii L.), under refiigeration (15± l0 C) and at ambient temperature (27±1°C). The fruits packed in LDPE with KMn04 ripened within 60 days after harvesting at week 12 from flower emergence. This was followed by fruits packed in LDPE without KMn04 (54 days), clingwrap (42 days), liquid paraffin (36 days), control at 15°C (24 days) and control at ambient (18 days). The percentage weight loss, peel and pulp colours of fruits increased significantly (P<0.01) for all treatments during storage. On the other hand, the texture values and tannin content of the fruit decreased significantly (P<0.01) during storage. The rise in total soluble solids (TSS) and sugar were slow initially but gradually increase rapidly at the end of the storage period.